Kinematics of the ankle joint complex in snowboarding - Delorme, S.; Tavoularis, S.; Lamontagne, M. (Journal of Applied Biomechanics, 2005)
Because snowboarders are known to injure their ankles more often than Alpine skiers, it has been postulated that stiffer snowboard boots would provide better protection to the ankle than current soft boots do. Snowboarders are also known to injure their front ankle more often than their back ankle, presumably because of the asymmetrical rotations of the ankles due to asymmetrical binding adjustement. To test these hypotheses, we measured the kinematics of the feet and legs of 5 snowboarders wearing soft boots and stiffer step-in boots during snowboarding maneuvers using an electromagnetic motion tracking system. The results were expressed in anatomically relevant rotations of the ankle joint complex, namely dorsi-/plantar flexion, eversion/inversion, and internal/external rotation. The measured ankle rotations show differences in the movement patterns of the front and back legs. Step-in boots were shown to allow less dorsiflexion, eversion, and external rotation than softer boots, possibly explaining why they are associated with a lower rate of fractures of the talus than soft boots.